Risks of postmetachronous malignancies in patients with Hodgkin lymphoma after radio- and chemotherapy - A. A. Danilenko; S. V. Shakhtarina; V. V. Pavlov (Онкогематология, 2016)
Introduction. Cure rate of patients with Hodgkin lymphoma (HL) is high by present. Further survival increase can be achieved by reducing mortality from late complications primarily from postmetahronous malignancies. Primary multiple malignant tumor become a problem for all cancer, including HL.Materials and methods. The study included 2137 patients with primary I, II, IIIs, IV (epiphrenic lesion) stages HL who received treatment at the Medical Radiological Research Center from 1968 to 2013 years. The diagnosis was verified morphologically. At the time of treatment start the patient age was 13–69 years, before 30 years of age were 1609 (75.3 %) patients. Women were 1412 (66 %), men – 725 (34 %). The main condition for patient inclusion was the amount of irradiation, limited lymph areas above the diaphragm and spleen. Patients were divided into 3 groups depending on method and period of treatment. 1st group – 363 patients received treatment from 1968 to 1977 consisting of independent radiation therapy (RT) according to “radical” program– irradiation of lymphatic collectors above the diaphragm and spleen (in case without splenectomy) with 40 Gy total focal dose. 2nd group – 1426 patients received treatment from 1978 to 1998 consisting of radiochemotherapy. Chemotherapy (CT) was performed according to COPP, CVPP. RT volume and total focal dose were identical to those of independent RT according to “radical” program. 3rd group – 348 patients received treatment from 1999 to 2013 consisting of CT according to first-line scheme and RT of lesions and related areas with reduced total focal dose (20–30 Gy) exposure.Multifield RT was used. To calculate the incidence of postmetachronous malignancies counted the number of patients/years of observation after HL treatment by age-appropriate five-year intervals and depending on gender. Incidence of malignant tumors in Russian population obtained from journal “Bulletin of the NN Blokhin Russian Cancer Research Center”. The expected incidence of postmetachronous tumors in HL patients calculated in each age group according to gender. The relative risk of  postmetachronous malignant tumors in HL patients was determined by the ratio of observed to expected incidence. 95 % confidence interval is calculated by J.  Vandenbroucke method.Results. Follow-up duration after HL treatment was 6 months–36 years (median – 18 years) in the 1st group, 7 months–28 years (median – 14 years) in the 2nd group and 1–17 years (median – 7 years) in the 3rd group. The number of patients/years of observation was 5562 in the 1st group, 13387 – in the 2nd group and 1906 – in the 3rd group. Postmetachronous malignancies were diagnosed in 87 (4.1 %) from 2137 patients: in 27/363 (7.4 %) in the 1st group, in 53/1426 (3.7 %) – in the 2nd group and in 7/348 (2 %) – in the 3rd group. One postmetachronous malignant tumor diagnosed in 81 patients, in 5 patients – 2 tumors and in 1 patient – 3 tumors  appeared consistently. Total number of postmetachronous malignancies was 94 (33 – after radiotherapy, 61 – after chemotherapy), from which solid tumors were 90(95.7 %) and leukemia – 4 (4.3 %). Time of tumor diagnosis after HL treatment ranged from 1 to 31 years. In exposed to radiation areas were upper respiratory tract tumors (3 cases), thyroid tumors (11 cases), salivary gland tumors (2 cases), soft tissues tumors of anterior chest wall (2 cases), skin tumors (2 cases) – total 20 from 94 malignancies (21.3 %). The relative risk of postmetachronous malignancies calculated only for patients of the 1st and the 2nd group (1789 pts, 18,949 pts/years of observation) due to short followup of patients receiving chemoradiotherapy with reduced total focal doses (the 3rd group). In case of radio- and radiochemotherapy with 40 Gy total focal dose the relative risk of postmetachronous malignancies was 2.84 (95 % confidence interval (CI) 1.85–2.98); for women – 3.01 (95 % CI 1.9–3.12), for men – 2.45 (95 % CI 1.23–2.91). In women the relative risk of postmetachrinous malignancies was 3.22(95 % CI 2.11–4.75) after independent RT and 2.89 (95 % CI 1.48–3.02) after radiochemotherapy; in man – 2.51 (95 % CI 0.9–4.63) and 2.44 (95 % CI 1.04–2.96), respectively. The relative risk common tumors: breast cancer – 4.01 (95 % CI 2.46–5.98); stomach cancer in women – 7.95 (95 % CI 3.2–14.4), stomach cancer in man – 4.03 (95 % CI 1.0–9.0); thyroid cancer in women – 7.81 (95 % CI 3.47–13.9).Conclusion. Patients with HL are at higher risk of developing malignant neoplasms, compared with general population. They require medical follow-up in order to identify not only HL relapse, but postmetahronous malignancies.